Pengaruh Perceived Quality Terhadap Kepuasan Pengunjung di Museum Mandala Wangsit Siliwangi - Suryani, Cynthiawati Suci; Andari, Rini; Taufik, Abdullah (THE Journal : Tourism and Hospitality Essentials Journal, 2018)
This study aims to determine and analyze the factors that affect Perceived Quality in Mandala Wangsit Silliwangi Museum. Mandala Wangsit Siliwangi Museum is one of the tourist destinations in Bandung with the theme ofÂ history museum in Bandung city visited by both domestic tourists and foreign tourists. Based on data acquisition, it is known that the visit to Mandala Wangsit Siliwangi Museum has decreased, even in 2016 2017 there was a very drastic decrease of visit. One of the factors that caused the decrease of the visit was due to the low Satisfaction of tourists at Mandala Wangsit Siliwangi Museum. Visitor Satisfaction is one of the important aspects of tourist destinations. In this study, the independent variable (X) used is Perceived Quality which consists of Service Interaction, Service Evidence, Product Functionality and Product Enrichment. The dependent variable (Y) used is Visitor Satisfaction. The type of this research is descriptive verification. The method used is a survey using systematic random sampling technique with the number of respondents as much as 100 respondents who visited the Mandala Wangsit Siliwangi Museum. Data analysis technique and hypothesis test used is Multiple Regression. The results showed that Perceived Quality gives a significant influence on visitor satisfaction. The biggest influence on visitor Satisfaction at Mandala Wangsit Siliwangi Museum is Service Interaction. The lowest effect on the visiting decision is Product Enrichment; this aspect needs to be improved in activity on Product Enrichment.